Computational investigation of the transient cyclic thermal distortion of funnel shaped mould in thin slab continuous casting process. (1st December 2022) - Jayakrishna, Pedduri; Chakraborty, Saurav; Ganguly, Suvankar; Talukdar, Prabal
Graphical abstract: Highlights: Distortion of funnel shaped mould is determined using 3D thermal-elastic–plastic-creep model in thin slab continuous casting. Excluding creep model overestimates the mould distortion. Cyclic variations in the mould distortion during heating and cooling operations. Performing multiple cycles is essential for accurate estimation of mould distortion. Abstract: The response of the thin slab continuous casting mould subjected to thermal and mechanical interactions needs to be studied, since they alter the shape of the mould. A 3D thermomechanical model is developed using non-linear kinematic and isotropic plasticity models along with the creep model to calculate the transient cyclic distortion, residual stress, and elastic–plastic-creep strains in an assembly of funnel-shaped copper mould and waterbox, as the mould undergoes multiple heating cycles in its lifetime. Most of the funnel transition region of the wide face is accumulated with higher temperatures and hence, displacements and strain distributions are maximum in that region. Distortion of the narrow face is majorly affected by the mechanical boundary condition. It is observed that excluding the time dependent creep model highly overestimated the mechanical behaviour of the mould. It is also observed that there is a cyclic variation of distortion of the mould towards the liquid metal side during the casting process and away from the liquid metal side during the cooling process which causes the development of residual stresses inside the mould. This phenomenon further leads to reduction in the magnitude of distortion during subsequent heating cycles of casting operation.